Influence of resilient obturator material on self reported obturator function in individuals with maxillectomies (2022)
Removable maxillary obturators are the standard of care in rehabilitating individuals who have had maxillectomies in most specialist healthcare facilities in Nigeria. The rehabilitation of these individuals should emphasise quality of life rather than normative standards by the healthcare professional. This study sought to examine the relationship, if any, between the materials used for obturator fabrication and self- perceived quality of life as reported by the individuals rehabilitated. Materials and methods: Twelve individuals with maxillary defects participated in the trial. They were provided with two definitive obturators each after undergoing post surgical rehabilitation. One of the obturators had a hollow all acrylic bulb while the other had a hollow acrylic bulb with an outer layer of silicone resilient denture liner. The participants wore each prosthesis for a two - week period and crossed over to the other without wash out. The adapted Obturator Functioning Scale questionnaire was administered after the patient had worn each prosthesis. Paired t-test was employed to compare mean obturator functioning scores.